2014
DOI: 10.1016/j.jmoldx.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Rapid Detection of Chlamydia trachomatis by Recombinase Polymerase Amplification Directly from Urine Samples

Abstract: Chlamydia trachomatis is the most common sexually transmitted human pathogen. Infection results in minimal to no symptoms in approximately two-thirds of women and therefore often goes undiagnosed. C. trachomatis infections are a major public health concern because of the potential severe long-term consequences, including an increased risk of ectopic pregnancy, chronic pelvic pain, and infertility. To date, several point-of-care tests have been developed for C. trachomatis diagnostics. Although many of them are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 30 publications
4
95
0
Order By: Relevance
“…The most frequently isolated STD pathogen was C. trachomatis (frequency of 32.69%, see Table I). Other studies also reported C. trachomatis as the most prevalent bacterial STD (26,28). Next two in the prevalence scale, U. urealyticum and N. gonorrhoeae (frequency of 17.31% and 13.46%), were found in relatively equal proportions, a finding also consistent with prevalence studies conducted in other countries (27,29).…”
Section: Distribution Of Std Pathogens In the Study Groupsupporting
confidence: 82%
“…The most frequently isolated STD pathogen was C. trachomatis (frequency of 32.69%, see Table I). Other studies also reported C. trachomatis as the most prevalent bacterial STD (26,28). Next two in the prevalence scale, U. urealyticum and N. gonorrhoeae (frequency of 17.31% and 13.46%), were found in relatively equal proportions, a finding also consistent with prevalence studies conducted in other countries (27,29).…”
Section: Distribution Of Std Pathogens In the Study Groupsupporting
confidence: 82%
“…3 Recombinase polymerase amplification (RPA) offers significant advantages over other isothermal amplification techniques for point-of-care applications: it requires a lower amplification temperature, is tolerant to impure samples, amplifies targets to detectable levels within minutes, and uses lyophilized enzymes to enable storage and transport at room temperature. 4,5 For these reasons, a number of recent reports have proposed RPA-based strategies for the detection of pathogens. [6][7][8][9][10] Although some papers demonstrate a relationship between nucleic acid concentration and onset of amplification, 10,11 to the best of our knowledge, RPA has not yet been implemented to quantify sample concentration using a standard curve.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RPA has demonstrated a certain tolerance to common PCR inhibitors [6], minimizing sample preparation requirements. The present study showed that genomic DNA or RNA, obtained from the urine and stool samples by direct dilution and boiling, could be successfully used as the template of RPA [7,12]. Our laboratory is also focusing on the simple and rapid genomic extraction to make RPA a useful in-field and point-of-care diagnostic technique.…”
mentioning
confidence: 77%